STUDI PENENTUAN TINGKAT ISOLASI DASAR TRANSFORMATOR MELALUI SIMULASI NUMERIK - Surya Saputra, Wasimudin
Abstract : If an electrical equipment like power transformers has a modification, maybe the Basic Insulation Level (BIL) of the equipment mentioned will be changed. To decide the new value of the BIL is very complicated. According to the IEC Standards, the BIL of an equipment is defined as an insulation strength of equipment against peak value of impulse voltage 1,2/50 ps. However, for the modified power transformers, the Standard is impossible to apply because the impulse test on power transformers is type test. It means that it can be done on the sample and it is considered as the destruction test. This paper describes a method to estimate the BIL of power transformers through numeric simulation. For the need mentioned, a pro-rated of single phase transformers is made. This pro-rated consists of high and low voltage winding which has 24 turns each. The numeric model which represented transient conditions of this pro-rated is validated with the result of the impulse voltage application experiment from the hybrid generator 3 kV 1,2/50 ps source. In the hope of getting a numeric model that can be used to evaluate the BIL of this pro-rated and it can he used to the real transformers, the result of experiment and EAITP simulation are compared.